2008
DOI: 10.1002/ajh.21151
|View full text |Cite
|
Sign up to set email alerts
|

Hematological abnormalities in patients with distal renal tubular acidosis and hemoglobinopathies

Abstract: Mutations of the human SLC4A1 gene encoding erythroid and kidney isoforms of anion exchanger 1 (AE1, band 3) result in erythrocyte abnormalities or distal renal tubular acidosis (dRTA) and such mutations are observed in Southeast Asia, where hemoglobinopathies are prevalent. Genetic and hematological studies in 18 Thai patients with dRTA have shown that 12 of them (67%) carried SLC4A1 mutations (7 G701D/G701D, 3 SAO/G701D, and 2 G701D/A858D). Of these 12 patients, three had homozygous G701D/G701D and heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…1) and the 3 homozygous G701D patients in this study, 3, 5a and 5b, were initially misdiagnosed as SAO from their blood smears. This ovalocytic morphology in homozygous G701D red cells has been reported from Thailand [4,14] and our data confirm that it is typical of the homozygous G701D phenotype. Although we found up to 50% of ovalocytes in the blood film red cells of our 3 homozygous G701D patients, close study of these films suggested that stomatocytes and macrocytes were less common in this syndrome than in SAO; these changes are scanty in fig.…”
Section: Methods and Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1) and the 3 homozygous G701D patients in this study, 3, 5a and 5b, were initially misdiagnosed as SAO from their blood smears. This ovalocytic morphology in homozygous G701D red cells has been reported from Thailand [4,14] and our data confirm that it is typical of the homozygous G701D phenotype. Although we found up to 50% of ovalocytes in the blood film red cells of our 3 homozygous G701D patients, close study of these films suggested that stomatocytes and macrocytes were less common in this syndrome than in SAO; these changes are scanty in fig.…”
Section: Methods and Resultssupporting
confidence: 91%
“…G701D homozygotes and G701D/SAO compound heterozygotes were both moderately anaemic initially (table 1), suggesting excess haemolysis, as has been reported previously in G701D/SAO and G701D/G701D [3,14], but unexpectedly the red cells from both groups of patients appeared to have SAO morphology (fig. 1) and the 3 homozygous G701D patients in this study, 3, 5a and 5b, were initially misdiagnosed as SAO from their blood smears.…”
Section: Methods and Resultssupporting
confidence: 73%
See 3 more Smart Citations